FcgiOCSP: a scalable OCSP‐based certificate validation system exploiting the FastCGI interface. (6th August 2012) - Berbecaru, Diana; Casalino, Matteo M.; Lioy, Antonio
SUMMARY: Certificate validation, one of the most important and complex tasks in Public Key Infrastructures, is still a challenging topic nowadays because of the scalability and complexity issues related to this process. Validation of an X.509 certificate requires checking its revocation status, either by consulting the so‐called Certificate Revocation Lists or by contacting a specific server via the Online Certificate Status Protocol (OCSP). Because more and more entities extensively need to validate the certificates used for various purposes (such as digital signature, server authentication, and secure e‐mail), the OCSP servers become overloaded. Thus, an increasing effort is currently dedicated to the creation and management of scalable certificate validation architectures. In this work, we discuss scalability challenges in OCSP‐based certificate validation, and we propose a method to evaluate the OCSP server performance in stress conditions. Next, we experimentally measure the performance, expressed in terms of response time and throughput, of some open‐source OCSP implementations. Finally, we propose and evaluate our own scalable OCSP‐based certificate validation system, named FcgiOCSP, as it exploits the FastCGI interface. Experimental results demonstrate the high performance of FcgiOCSP with respect to other OCSP implementations evaluated in this work. Copyright © 2012 John Wiley & Sons, Ltd.